Desarrollo de sistema de clasificación de color y apariencia de chontaduro para exportación en la finca el Cedro de Villa Garzón (Putumayo) utilizando procesamiento de imágenes. - Marín Rojas, Jaiderne (Universidad Antonio Nariño, 2024)
The Image processing for use in fruit classification process is an effective method to mitigate returns in the export process, this solution not only contributes in the classification, but also in the simplification of errors, costs and product damage; this project aims to develop the classification system of color and appearance of chontaduro for export, in the farm the cedar of Villa Garzón (Putumayo) through image processing.